Light extraction efficiency enhancement of flip-chip blue light-emitting diodes by anodic aluminum oxide - Huang, Yi-Ru; Chiu, Yao-Ching; Huang, Kuan-Chieh; Ting, Shao-Ying; Chiang, Po-Jui; Lai, Chih-Ming; Jen, Chun-Ping; Tseng, Snow H.; Wang, Hsiang-Chen (Beilstein Journal of Nanotechnology, 2018)
We produced an anodic aluminum oxide (AAO) structure with periodic nanopores on the surface of flip-chip blue light-emitting diodes (FC-BLEDs). The nanopores had diameters ranging from 73 to 85 nm and were separated by distances ranging from approximately 10 to 15 nm. The light extraction efficiency enhancement of the FC-BLEDs subjected to different durations of the second pore-widening process was approximately 1.6–2.9%. The efficiency enhancement may be attributed to the following mechanism: periodic nanopores on the surface of FC-BLEDs reduce the critical angle of total reflection and effective energy transfer from a light emitter into a surface plasmon mode produced by AAO.
Keywords: anodic aluminum oxide; critical angle of total reflection; efficiency enhancement; flip-chip blue light-emitting diode

(untitled) - Schubert, E. F.; Kim, J. K. (Science, 2005)

(untitled) - Taguchi, T.; Uchida, Y.; Kobashi, K. (Phys. Status Solidi, 2004)

(untitled) - Okamoto, K.; Kawakami, Y. (IEEE J. Sel. Top. Quantum Electron., 2009)

(untitled) - Pimputkar, S.; Speck, J. S.; DenBaars, S. P.; Nakamura, S. (Nat. Photonics, 2009)

Proceedings of the 2007 33rd European Conference and Exhibition of Optical Communication - Grubor, J.; Lee, S. C. J.; Langer, K.-D.; Koonen, T.; Walewski, J. W. (Wireless High-Speed Data Transmission with Phosphorescent White-Light LEDs, Berlin, Germany, 16.9.2007-20.9.2007, 2008)

(untitled) - Chen, F.; Wang, K.; Qin, Z.; Wu, D.; Luo, X.; Liu, S. (Opt. Express, 2010)

(untitled) - Lin, R. J.; sai, M.-S.; Sun, C.-C. (Opt. Express, 2015)

(untitled) - Huang, K.-C.; Huang, Y.-R.; Tseng, C.-M.; Tseng, S.-H.; Huang, J.-E. (Scr. Mater., 2015)

(untitled) - Vannahme, C.; Dufva, M.; Kristensen, A. (Light: Sci. Appl., 2015)

U.S. Patent Application - Ryu, K. H.; Kim, H. Y.; Kim, S. K.; Lee, Y. J.; Min, S. H. (Inorganic particle scattering film having a good light-extraction performance, 2011)

(untitled) - Ding, Q.-a.; Li, K.; Kong, F.; Chen, X.; Zhao, J. (J. Disp. Technol., 2014)

(untitled) - Shei, S.-C. (IEEE J. Quantum Electron., 2014)

(untitled) - Li, X.-H.; Zhu, P.; Liu, G.; Zhang, J.; Song, R.; Ee, Y.-K.; Kumnorkaew, P.; Gilchris, J.-F.; Tansu, N. (J. Disp. Technol., 2013)

(untitled) - Lee, C.-Y.; Huang, C.-C.; Lia, C.-L.; Chang, Y.-F.; Chen, S.-F.; Ho, C.-L.; Liu, J.-Z.; Wu, M.-C. (IEEE Electron Device Lett., 2013)

(untitled) - Ryu, S.-W.; Park, J.; Oh, J.-K.; Long, D. H.; Kwon, K.-W.; Kim, Y.-H.; Lee, J. K.; Kim, J. H. (Adv. Funct. Mater., 2009)

(untitled) - Cates, J. W.; Hayward, J. P.; Zhang, X. (IEEE Trans. Nucl. Sci., 2013)

(untitled) - Jewell, J.; Simeonov, D.; Huang, S.-C.; Hu, Y.-L.; Nakamura, S.; Speck, J.; Weisbuch, C. (Appl. Phys. Lett., 2012)

(untitled) - McGroddy, K.; Davida, A.; Matioli, E.; Iza, M.; Nakamura, S.; DenBaars, S.; Speck, J. S.; Weisbuch, C.; Hu, E. L. (Appl. Phys. Lett., 2008)

(untitled) - Zhu, P.; Liu, G.; Zhang, J.; Tansu, N. (J. Disp. Technol., 2013)

(untitled) - Zhu, P.; Tansu, N. (Photonics Res., 2015)

(untitled) - Zhu, P.; Tansu, N. (Appl. Opt., 2015)

(untitled) - Zhu, P.; Tan, C.-K.; Sun, W.; Tansu, N. (Appl. Opt., 2015)

(untitled) - Koo, W. H.; Youn, W.; Zhu, P.; Li, X.-H.; Tansu, N.; So, F. (Adv. Funct. Mater., 2012)

(untitled) - Zhu, P. (Mater. Res. Express, 2015)

(untitled) - Zhu, P. (J. Opt. (Bristol, U. K.), 2016)

(untitled) - Jiang, S.; Feng, Y.; Chen, Z.; Zhang, L.; Jiang, X.; Jiao, Q.; Li, J.; Chen, Y.; Li, D.; Liu, L.; Yu, T.; Shen, B.; et al. (Sci. Rep., 2016)

(untitled) - Wang, X.; Han, G.-R. (Microelectron. Eng., 2003)

(untitled) - Kang, G.; Bae, K.; Nam, M.; Ko, D.-H.; Kim, K.; Padilla, W. J. (Energy Environ. Sci., 2015)

(untitled) - Han, D.-S.; Kim, J.-Y.; Na, S.-I.; Kim, S.-H.; Lee, K.-D.; Kim, B.; Park, S.-J. (IEEE Photonics Technol. Lett., 2006)

(untitled) - Nakamura, S.; Mukai, T.; Senoh, M. (Appl. Phys. Lett., 1994)

(untitled) - Wang, W.-K.; Wu, D.-S.; Lin, S.-H.; Huang, S.-Y.; Han, P.; Horng, R.-H. (Jpn. J. Appl. Phys., 2006)

(untitled) - Lee, J.-H.; Hwang, S.-M.; Kim, N.-S.; Lee, J.-H. (IEEE Electron Device Lett., 2010)

(untitled) - Cheng, B.-S.; Lee, C.-E.; Kuo, H.-C.; Lu, T.-C.; Wang, S.-C. (Jpn. J. Appl. Phys., 2009)

(untitled) - Shen, C. F.; Chang, S. J.; Chen, W. S.; Ko, T. K.; Kuo, C. T.; Shei, S. C. (IEEE Photonics Technol. Lett., 2007)

(untitled) - Joo, D. H.; Lee, H. K.; Yu, J. S. (IEEE Photonics Technol. Lett., 2012)

(untitled) - Baek, S.; Kang, G.; Shin, D.; Bae, K.; Kim, Y. H.; Kim, K. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Mattiucci, N.; D’Aguanno, G.; Everitt, H. O.; Foreman, J. V.; Callahan, J. M.; Buncick, M. C.; Bloemer, M. J. (Opt. Express, 2012)

(untitled) - Hao, Q.; Wang, C.; Huang, H.; Li, W.; Du, D.; Han, D.; Qiu, T.; Chu, P. K. (Sci. Rep., 2015)

(untitled) - Okamoto, K.; Niki, I.; Shvartser, A.; Narukawa, Y.; Mukai, T.; Scherer, A. (Nat. Mater., 2004)

(untitled) - Kwon, M.-K.; Kim, J.-Y.; Kim, B.-H.; Park, I.-K.; Cho, C.-Y.; Byeon, C. C.; Park, S.-J. (Adv. Mater., 2008)

(untitled) - Wang, H.-C.; Yu, X.-Y.; Chueh, Y.-L.; Malinauskas, T.; Jarasiunas, K.; Feng, S.-W. (Opt. Express, 2011)

(untitled) - Kuo, Y.; Chang, W.-Y.; Lin, C.-H.; Yang, C.-C.; Kiang, Y.-W. (Opt. Express, 2015)

(untitled) - Lin, C.-H.; Chen, C.-H.; Yao, Y.-F.; Su, C.-Y.; Shih, P.-Y.; Chen, H.-S.; Hsieh, C.; Kuo, Y.; Kiang, Y.-W.; Yang, C. C. (Plasmonics, 2015)

(untitled) - Kuo, Y.; Su, C.-Y.; Hsieh, C.; Chang, W.-Y.; Huang, C.-A.; Kiang, Y.-W.; Yang, C. C. (Opt. Lett., 2015)

(untitled) - Kuo, Y.; Yao, Y.-F.; Chiu, M.-H.; Chang, W.-Y.; Yang, C. C.; Kiang, Y.-W. (Plasmonics, 2015)

(untitled) - Moharam, M. G.; Pommet, D. A.; Grann, E. B.; Gaylord, T. K. (J. Opt. Soc. Am. A, 1995)

(untitled) - Masuda, H.; Fukuda, K. (Science, 1995)

(untitled) - Feiyue, L.; Zhang, L.; Metzger, R. M. (Chem. Mater., 1998)

(untitled) - Poinern, G. E. J.; Ali, N.; Fawcett, D. (Materials, 2011)